Theatre & the body - Conroy, Colette, 1973- (Theatre&., 2010)
"Bodies are active and dynamic elements of theatre production and spectatorship. They are important concepts as well as objects within theater. This book examines the rich and complex relationships between the uses of bodies in theater and the ways in which bodies are culturally imagined and understood in theater"--Provided by publisher.